Slip‐Stacked J‐Aggregate Materials for Organic Solar Cells and Photodetectors (Adv. Mater. 22/2022). Issue 22 (2nd June 2022) - Kim, Jin Hong; Schembri, Tim; Bialas, David; Stolte, Matthias; Würthner, Frank
Abstract : Organic Photovoltaics Slip‐stacked J‐aggregate materials feature unique optical and electronical properties for organic solar cells and photodetectors, requiring either broad‐ or narrowband absorbance. In article number 2104678, Frank Würthner and co‐workers classify different cases of J‐type coupling for different classes of dyes and correlate their optical properties with their characteristic packing arrangements.